SAT0542 European Chart Review Study on Early Rheumatoid Arthritis (RA): Patient Profile and Biologic Treatment Patterns. (23rd January 2014) - Emery, P.; Solem, C. T.; McGuire, M. B.; Majer, I.; Hensen, M.; Stephens, J. M.; Tarallo, M.
Abstract : Background: The availability of new biologic treatments that directly target components of the RA inflammatory cascade had transformed management of this disease over the last 10 years. While these agents have been shown to improve laboratory and clinical measures of disease activity, they are also significantly more expensive than oral disease-modifying anti-rheumatic drugs (DMARDs) and are thus typically reserved for patients with severe disease or who have failed DMARD therapy. Objectives: To describe biologic treatment patterns for RA, including patient and clinical characteristics at the initiation of therapy and drug selection, in Germany (GE), Spain (SP), and the United Kingdom (UK). Methods: This retrospective, observational medical chart review study captured patient data via 118 rheumatologists across the three study countries. Patients ≥18 years, with a confirmed diagnosis of RA between January 2008 and December 2010, who received a biologic therapy for at least three months and had at least 12 months of follow-up were included. Data collected for analysis of prescribing patterns included patient characteristics (age, gender, employment status, comorbid conditions), disease information (date of diagnosis, Disease Activity Score [DAS]), and drug therapy received (drug, dose and frequency, dates of initiation and discontinuation). Early treatment was defined as initiation of a biologic agent within one year of RA diagnosis. Compliance with reimbursement guidelines for each country (DAS >5.2 [UK] or >3.2 [SP] at initiation of biologic therapy; no national threshold for GE) was also assessed. Results: A total of 328 patients were enrolled in the study across GE (n=111), SP (n=106), and UK (n=111). The mean age was 48 years, and 70% of patients were female. Only 44% of patients were employed on a full-time basis. Approximately half of the study patients had at least one comorbid condition, with the most common being depression (13%), osteoarthritis (13%), and osteoporosis (12%). Over half of patients (58%) received early biologic treatment, and frequency did not differ significantly by country (GE – 55%, SP – 64%, UK – 56%). In 19.4% of patients with complete treatment information from diagnosis (N=299), biologic therapy was not preceded by DMARDs, corticosteroids, or prescription NSAIDs; first-line biologics were prescribed more frequently in SP (26%) and GE (20%) compared to UK (7%; p=0.001). The most commonly prescribed initial biologics were adalimumab (40.6%), etanercept (37.8%), and infliximab (7.0%). Mean DAS-28 at the time of initiation of biologic therapy was 5.5, 4.7, and 5.2 in UK, SP, and GE, respectively; this score was above the minimum required for reimbursement in 78% of patients in UK and 87% in SP. Conclusions: This study of real-world treatment patterns found that over half of patients with RA in GE, SP, and UK are treated with biologic therapy within one year of diagnosis. Biologics are used as initial treatment more frequently in SP and GE than in UK. Etanercept and adalimumab comprise nearly 80% of biologic use across all countries. In countries with explicit guidelines for initiation of biologic therapy by DAS, these guidelines were generally followed. Disclosure of Interest: P. Emery Consultant for: Pfizer, C. Solem Consultant for: Pfizer, Employee of: Pharmerit International, M. McGuire Consultant for: Pfizer, Employee of: Medical Data Analytics, I. Majer Consultant for: Pfizer, Employee of: Pharmerit International, M. Hensen Consultant for: Pfizer, Employee of: Pharmerit International, J. Stephens Consultant for: Pfizer, Employee of: Pharmerit International, M. Tarallo Employee of: Pfizer